Developing Local-Based English for Tourism Material for Religious and Cultural Tour Guide Program Students: A Needs Analysis - Muthia Farida (ENLIT, 2022)
Teaching ESP requires a thorough and systematic way in developing the materials because the purpose is to help students develop their English competence in specific disciplines. What was found in the teaching of English for Tourism in the Religious and Cultural Tour Guide Program in Tampung Penyang State Hindu Institute (IAHN) of Palangka Raya was the absence of proper materials for the students. This study is a small part of Research and Development (RnD) project for an English for Tourism book of this faculty. It involved the stakeholder and the practitioner in the local tourism industry as the informants in giving insights to local-based material development. Employing a qualitative approach, the in-depth interviews were conducted. The results of this study finally offer some recommendation for English for Tourism materials: 1) speaking and writing as the top priorities of required English skills, 2) language functions included: self-introduction, negotiating, handling tourists at an airport, making an itinerary, writing and replaying an email, and describing tourist destination or place, 3) vocabulary related to tourism industry and especially tour guiding, 4) cross-cultural understanding, and 5) local tourist destinations.